2004
DOI: 10.3748/wjg.v10.i18.2731
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl disulfide-induced G2/M arrest of human gastric cancer MGC803 cells involves activation of p38 MAP kinase pathways

Abstract: DADS-induced G2/M arrest of MGC803 cells involves activation of p38 MAP kinase pathways. Decreased Cdc25C protein expression by p38 MAPK played a crucial role in G2/M arrest after treatment with DADS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 34 publications
1
45
1
Order By: Relevance
“…recent studies have reported that the ability of dadS to up-or down-regulate the mrna expression of some genes is related to its signal pathway (17)(18)(19)(20)46). our results revealed that dadS may be involved in mediating multiple signal pathways in HT-29 cells by up-regulating the expression of GPCR175, GNB1, PSMD12, S100A6, TACSTD2 or by suppressing ATP1A1, YWHAE and FLJ25150 fis.…”
Section: Discussionsupporting
confidence: 51%
“…recent studies have reported that the ability of dadS to up-or down-regulate the mrna expression of some genes is related to its signal pathway (17)(18)(19)(20)46). our results revealed that dadS may be involved in mediating multiple signal pathways in HT-29 cells by up-regulating the expression of GPCR175, GNB1, PSMD12, S100A6, TACSTD2 or by suppressing ATP1A1, YWHAE and FLJ25150 fis.…”
Section: Discussionsupporting
confidence: 51%
“…A decreased Cdc25C expression plays a crucial role in G 2 /M arrest after treatment with DADS (19). In the current study, DADS was shown to induce phosphorylation of ATR (ATM-RAD3-related gene) and Chk, while suppressing expression of Cdc25C and cyclin B1 in the human gastric cancer cell line BGC823.…”
Section: Introductionmentioning
confidence: 74%
“…The MTT assay was performed using the method of Yuan et al (19). Briefly, a 200-μL suspension containing approximately 2 x 10 4 cells was added to each well of a 96-well culture plate and incubated for 24 h at 37°C in a humidified atmosphere of 95% air and 5% CO 2 .…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that diallyldisulfide and, in some cases diallyltrisulfide, cause mitotic arrest in cancer cells (7)(8)(9). Interestingly, these organosulphur compounds do not only inhibit cancer cell proliferation but also appear to induce apoptosis in cancer cells, which apart from chemo-preventive aspects turns these agents into interesting lead structures for the treatment of already existing cancers (10-13).…”
Section: Introductionmentioning
confidence: 99%